Legal Problems in Regional Financial Management Policy in Central Sulawesi Province - S, Irzha Friskanov.; Anandy, Widyatmi (Universitas Widya Gama Malang, 2024)
The Central Government makes full use of the resources assigned to the region in order to support the realization of regional autonomy, the effectiveness of the national economy, and the application of the principles of good governance, transparency, and accountability. The government increases professionalism, transparency, and responsibility in its administration as a manifestation of regional financial management. There is no denying that managing a nation and its government takes a lot of resources. How to handle regulations and issues pertaining to financial management in Central Sulawesi Province is the issue. The examination of statutory and doctrinal literature was prioritized in this research, which was undertaken utilizing normative legal research and analysis techniques. Deciding on policies while making use of legislative documents, contextual methods, and case approaches, as well as the broad concepts of the philosophy of power and government action. The community, as well as managers, supervisors, and regulators, work together to supervise regional financial management. The conclusion is that in order to achieve good governance and the involvement of local governments and people in achieving regional development goals, regional financial management strategies must incorporate openness and accountability.